2010
DOI: 10.1002/j.1556-6978.2010.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory of Counselor Educators Integrating Social Justice Into Their Pedagogy

Abstract: The topic of social justice has received considerable attention in the counseling literature; however, little empirical research exists. This grounded theory study examined 4 counselor educators' process of integrating social justice constructs into their pedagogy. Data analysis revealed 4 primary experiences that emerged in the participants' descriptions of their integration of social justice into their pedagogy. Implications for counselor educators and future research are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…With many of the postconventional thinkers appearing to be poised for advocacy, a third promising possibility for inquiry involves counselor educators instigating an action-oriented advocacy stance in students, including promoting an enhanced ability as systems change agents (D'Andrea and Daniels 2010; Odegard and Vereen 2010;Ratts and Wood 2011). For example, in the second author's doctoral multicultural course, students are required to engage in an extended immersion experience that includes advocacy action with their chosen cultural group.…”
Section: Future Inquiriesmentioning
confidence: 98%
“…With many of the postconventional thinkers appearing to be poised for advocacy, a third promising possibility for inquiry involves counselor educators instigating an action-oriented advocacy stance in students, including promoting an enhanced ability as systems change agents (D'Andrea and Daniels 2010; Odegard and Vereen 2010;Ratts and Wood 2011). For example, in the second author's doctoral multicultural course, students are required to engage in an extended immersion experience that includes advocacy action with their chosen cultural group.…”
Section: Future Inquiriesmentioning
confidence: 98%
“…Notwithstanding the ambivalence and misconceptions about the sociopolitical nature of social justice advocacy, or the dearth of evidence based strategies Brubaker, Puig, Reese, & Young, 2010;Odegard & Vereen, 2010;Ratts & Wood, 2011), there is compelling evidence to move forward decisively in integrating advocacy training in the counselor education curriculum (Decker, 2013;Manis, 2008;Paylo, 2007). Yet the task of preparing counselors to be social justice advocates may also seem daunting in terms of resources as universities confront limited and even reduced resources.…”
Section: Counselors and Advocacy: An Integrated Identitymentioning
confidence: 99%
“…Counselor educators should note that engagement in advocacy can be influenced through providing students with opportunities to practice and dialogue about social issues. Specifically, research has indicated that political interest and skills in navigating difficult conversations seem to be important factors for counselors to be able to enact advocacy behaviors Nilsson & Schmidt, 2005;Odegard & Vereen, 2010;Singh, Urbano, Haston, & McMahan, 2010). Likewise, advocates often report needing to be strategic and resilient in their work, since resistance to change may be inevitable (Arthur, Collins, McMahon, & Marshall, 2009;Lee et al, 2013;McWhirter, 1997;Sumner, 2013).…”
Section: Infusing Advocacy Into Counselor Trainingmentioning
confidence: 95%
“…From this perspective, social justice and advocacy interventions need to be practiced in both the content and the process of the counseling classroom. Several counselor educators have underscored the importance of structuring classroom activities and relationships in a way that does not recapitulate harmful hierarchies or maintain inaccurate assumptions about others but instead allows students to harness the experience of the group/class for deepened reflection and awareness (Adams et al, 2007;Brubaker, Puig, Reese, & Young, 2010;Manis, 2012;Odegard & Vereen, 2010). For example, social justice pedagogy should intentionally generate critical consciousness in students and encourage them to question norms, as opposed to receiving knowledge about social groups without questioning (Goodman et al, 2015).…”
Section: Introductionmentioning
confidence: 95%